The Position of Arbitration in Dispute Resolution of Islamic Financial Institutions - Adi Astiti, Ni Nyoman; Rahman, Ghozali; Ibtisamah, Siti Nur (AL-QARDH, 2021)
Arbitration in Islamic law is known as the term tahkim which comes from Arabic. Arbitration in Islam has been recognized in the Al-Qur